ОБЩАЯ ХАРАКТЕРИСТИКА СТАНОВЛЕНИЯ И РАЗВИТИЯ ЗАКОНОДАТЕЛЬСТВА О ЗЕМЛЯХ ГОРОДОВ (Journal of actual problems of jurisprudence, 2019)
In this article the author examines the stages of formation and development of legislation on urban land and their use andregulation.